1996
DOI: 10.1111/j.1365-2044.1996.tb14961.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulated difficult intubation

Abstract: SummaryA rundomised study M

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(11 citation statements)
references
References 13 publications
2
7
1
1
Order By: Relevance
“…However, applying cricoid pressure may cause difficulty with tracheal intubation by distorting larynx. 7 .In their study of 200 patients shows that overall Total Intubation time in Macintosh group was 34secs and in Truview group was 51secs.M.A.Mallik, C.H.Maharaja 8 .In their similar study of 120 patients shows the overall intubation time in Macintosh group was 13.9±9.2 secs, in the Truview group the Intubation time was 22.5±7.5 secs.Gataure, P. S., Vaughan et al 9 in a study of 100 patients found mean time taken for intubation in bogie group in first attempt was 14.4 sec and in second attempt it was 30.1 sec. It was 15.1 sec in first attempt and 36.6 sec in second attempt in stylet group.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, applying cricoid pressure may cause difficulty with tracheal intubation by distorting larynx. 7 .In their study of 200 patients shows that overall Total Intubation time in Macintosh group was 34secs and in Truview group was 51secs.M.A.Mallik, C.H.Maharaja 8 .In their similar study of 120 patients shows the overall intubation time in Macintosh group was 13.9±9.2 secs, in the Truview group the Intubation time was 22.5±7.5 secs.Gataure, P. S., Vaughan et al 9 in a study of 100 patients found mean time taken for intubation in bogie group in first attempt was 14.4 sec and in second attempt it was 30.1 sec. It was 15.1 sec in first attempt and 36.6 sec in second attempt in stylet group.…”
Section: Discussionmentioning
confidence: 93%
“…Nishant Kumar, KapilLamba et al 11 found that the Macintosh group 85% patients were intubated in the 1 st attempt and 15% patients were intubated in the 2 nd attempt, in the McCoy group 95% patients were intubated in the 1 st attempt and 5% patients were intubated in the 2 nd attempt, in the Truview group 85% patients were intubated in the 1 st attempt and 15% patients were intubated in the 2 nd attempt. Gataure, P. S.et al 9 shows that success rate at first attempt was 82%in bougie group and 48% in stylet group (p<0.001). Success rate after 2 attempts in the two groups were 96% and 66% respectively (p<0.001).…”
Section: Discussionmentioning
confidence: 94%
“…The GEB is a commonly used airway adjunct in intubation and is recommended by several guidelines for use at an early stage in cases of difficult intubation [ 6 , 7 ]. Evidence from adult patients suggests that anesthesiologists can secure the airway with a high success rate when using the GEB [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vielmehr glauben wir, dass die Zeit bis zur ETI in beiden Gruppen in einem Bereich liegt, der -berück-sichtigt man die Komplexität der RSI -eine deutliche Verkürzung nicht mehr zulässt. Hierfür sprechen die Zeiten bis zur ETI, wie sie in verschiedenen Studien angegeben werden [3,17]. Dabei zeigt sich, dass die Zeiten bis zur ETI in der vorliegenden Studie -bemerkenswerter Weise ohne Unterschied zwischen FÄ und WA -ohnehin relativ kurz sind.…”
Section: Tab 2 Zeit Bis Zum Ersten Adäquaten Laryngoskopiebefund (T unclassified